Engineering an incentive to search for work: A comparison groups approach - Oded Stark; Marcin Jakubek; Martyna Kobus (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
Social comparisons are important in the employment sphere. A "culture of unemployment" may evolve and prevail because it is optimal for an individual to remain unemployed when other unemployed individuals constitute his main reference group. We advance the idea that by making the receipt of unemployment benefits conditional on engagement in an incentive-enhancing activity (for example, work under state-sponsored employment schemes or participation in work-site-based training programs), a government can engineer a revision of the reference groups of an unemployed individual in order to induce him to seek work.
Keywords: D04; D69; H53; J22; J64; J65; 330; Unemployment benefits; Social comparisons; Relative deprivation